Analisis Keselamatan dan Kesehatan Kerja (K3) Dengan Metode Hazard And Operability Study (HAZOP) pada PT. Putra Agri Pas - Fatah, Muhammad Abdul; Putra, Fibi Eko; Heru, Heru (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
The aspect of Occupational Health and Safety (OHS) is a crucial factor that must be implemented across all industrial sectors, especially in production processes involving heavy machinery and high-risk physical activities. This study was conducted at PT. Putra Agri Pas with the aim of identifying potential hazards and assessing the level of occupational accident risks using the Hazard and Operability Study (HAZOP) approach. This method is applied to detect process deviations and to formulate appropriate preventive strategies. Data were collected through field observations and employee interviews, then analyzed using HAZOP worksheets and the Root Cause Analysis (RCA) method. The research findings indicate that most hazards fall into medium to high risk categories, primarily due to a lack of discipline in using personal protective equipment (PPE), insufficient safety training, and weak operational supervision. The study recommends enhancing control measures, conducting regular training sessions, and organizing the work environment to ensure a safer workplace.